2001
DOI: 10.1002/1521-4141(200201)32:1<87::aid-immu87>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

FCRL, a novel member of the leukocyte Fc receptor family possesses unique structural features

Abstract: A novel conserved member of the leukocyte Fc receptor (FcR) family was identified in human and mouse. The presumably secreted protein, designated FCRL (FcR‐like) is comprised of four domains. The three N‐terminal domains are related to the extracellular region of FcγRI, with the second (35–37% residue identity) and the third (46–52%) domains showing highest similarity. The C‐terminaldomain is a unique sequence enriched with proline residues. In humans, alternative transcripts for six FCRL isoforms were reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…Both genes contain potential STAT The organization of the low-affinity Fc␥R genes at chromosome 1q23. The assembly order and the orientation with regard to the centromere and telomere of the Fc␥R cluster genes and the nearby genes FcRL, 46,47 DUSP12 and ATF6 are shown. Duplication and deletion of Fc␥RIIIB have been described.…”
Section: Resultsmentioning
confidence: 99%
“…Both genes contain potential STAT The organization of the low-affinity Fc␥R genes at chromosome 1q23. The assembly order and the orientation with regard to the centromere and telomere of the Fc␥R cluster genes and the nearby genes FcRL, 46,47 DUSP12 and ATF6 are shown. Duplication and deletion of Fc␥RIIIB have been described.…”
Section: Resultsmentioning
confidence: 99%
“…Based on sequence features and genomic position, the gene encoding FREB2 is likely to be the gene predicted to exist and given the names FcRY 3 or FCRL2. 16 The cDNA and amino-acid sequences of human and mouse FREB2 are listed in Genbank under accession numbers AY786314 and AY513660.…”
Section: Freb2 Is a Member Of The Immunoglobulin Superfamily Homologomentioning
confidence: 99%
“…19 The existence of genes encoding other Fc receptor homologs in addition to these has been predicted. 3,16 In this study, we have identified a new Fc receptor homolog, FREB2, with immunoglobulin domains homologous to FcgRI, and a C-terminal domain previously thought to be unique to FREB1. Its expression within nonproliferating cells of the germinal center suggests a unique role for this protein in regulating B-cell differentiation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…After purification, the recombinant protein was suspended in sample buffer (0.1 M Tris-HCl, pH 6.8, 4% SDS, 20% glycerol, 1 M 2-mercaptoethanol). SDS-PAGE was carried out as described previously 28 and the separated proteins were blotted onto nitrocellulose membranes. The membranes were incubated with TBST-SM (137 mM NaCl, 2.68 mM KCl, 25 mM Tris-HCl, 0.02% Tween-20 containing 5% nonfat milk) at 4°C overnight.…”
Section: Western Blot Analysismentioning
confidence: 99%